Extraction, Characterization, and Chitosan Microencapsulation of Bioactive Compounds from Cannabis sativa L., Cannabis indica L., and Mitragyna speiosa K. - Srisan Phupaboon; Maharach Matra; Ronnachai Prommachart; Pajaree Totakul; Chanadol Supapong; Metha Wanapat (MDPI AG, 2022)
The objective of the research was to investigate the bioactive compounds of herbal plant leaves by microencapsulation technique for future application as a feed additive. In this experiment, three herbal plant leaves, namely Cannabis sativa L., Cannabis indica L., and Mitragyna speiosa K., were comparatively investigated using different methods to extract their bioactive compounds. Two methods were used to extract the bioactive compounds: microwave extraction (water-heating transferred) and maceration extraction (methanol extracted). The results obtained using microwave extraction revealed that the total polyphenolic and flavonoid contents and antioxidant capacity were significantly higher and stronger, respectively, than those produced by the maceration extraction method (p < 0.05). Furthermore, the spray-drying technique was employed to enhance the extracted compounds by encapsulation with chitosan through ionic gelation properties. The physical characteristics of chitosan-encapsulated substrates were examined under a scanning electron microscope (SEM) and were as microparticle size (1.45 to 11.0 µm). The encapsulation efficiency of the bioactive compounds was found to be 99.7, 82.3, and 54.6% for microencapsulated M. speiosa, C. indica, and C. sativa, respectively. Therefore, microwave treatment prior to chitosan encapsulation of leaf extracts resulted in increased recovery of bioactive compound encroachment.